2022
DOI: 10.1021/acsanm.2c04519
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrocatalytic Activity of Mo-Doped NiFe Layered Double Hydroxide Nanosheet Arrays for the Hydrogen Evolution Reaction

Abstract: NiFeMo layered double hydroxide (NiFeMo-LDH) nanosheet array structures in situ grown on Ni foam were rationally designed and fabricated by a convenient and green hydrothermal strategy. The systematic characterization proved that Ni x Fe 1 Mo 1 -LDH/NF (x = 4, 6, 8, 10) composites grew on the surface of Ni foam as vertically interlaced LDH nanosheets. The electrochemical results showed that all composites possessed high electrocatalytic activity, and Ni 6 Fe 1 Mo 1 -LDH/NF exhibited the best hydrogen evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…A detailed description for the synthesis of rGO/NF can be found in our previous work. [42][43][44][45] The SEM images show that bare Ni foam usually has a smooth surface, while rGO was uniformly coated on the NF surface in the rGO/ NF sample. It can be observed that the LDH nanosheets (size ∼135 nm × 15 nm) grew vertically and were interwoven on rGO/ NF.…”
Section: Electrocatalytic Performance Of the Novel Nicov 10 -Ldh/rgo/...mentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description for the synthesis of rGO/NF can be found in our previous work. [42][43][44][45] The SEM images show that bare Ni foam usually has a smooth surface, while rGO was uniformly coated on the NF surface in the rGO/ NF sample. It can be observed that the LDH nanosheets (size ∼135 nm × 15 nm) grew vertically and were interwoven on rGO/ NF.…”
Section: Electrocatalytic Performance Of the Novel Nicov 10 -Ldh/rgo/...mentioning
confidence: 99%
“…The results suggest that during the in situ growth process of NiCoV 1.0 -LDH/rGO/NF-100, more defect sites were created due to the reduction of GO in the alkaline reaction system. [42][43][44][45] The contact angle test results (Fig. S25b-e †) showed that the contact angle of NiCoV 1.0 -LDH/rGO/NF-100 (134.0°) was higher than those of NiCoV 1.0 -LDH/NF-100 (124.1°), rGO/NF-100 (96.2°), and NF (83.8°), suggesting a faster bubble release ability and improved catalytic activity.…”
Section: Electrocatalytic Performance Of the Novel Nicov 10 -Ldh/rgo/...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, non-precious metals such as Cu and Mo have been successfully introduced as dopants on NiFe oxide/hydroxides in the form of small clusters/ NPs [89] or as a third metal in the crystalline structure. [90,91] Consequently, exploring the use of non-precious metal-based SAs as dopants is a promising route to atomically tune the OER activity of NiFe oxide/hydroxides without the introduction of critical raw materials. Finally, the addition of a ligand in the NiFe oxide/hydroxide electrocatalyst (both on the surface and in the interlayer in the case of the LDH) has proven to be an effective strategy to induce second coordination sphere effects, especially important to accelerate the different proton coupled electron transfers taking place during the catalytic cycle (Scheme 1).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reported examples following this strategy are based on noble metal SAs. However, non‐precious metals such as Cu and Mo have been successfully introduced as dopants on NiFe oxide/hydroxides in the form of small clusters/NPs [89] or as a third metal in the crystalline structure [90,91] . Consequently, exploring the use of non‐precious metal‐based SAs as dopants is a promising route to atomically tune the OER activity of NiFe oxide/hydroxides without the introduction of critical raw materials.…”
Section: Discussionmentioning
confidence: 99%